Memahami Konsep “Ciptaan Baru” di dalam 2 Korintus 5:17 - Simon Simaremare (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2019)
Abstract The word "new creation" appears twice in the Bible, and is only found in Paul's writings, namely in 2 Corinthians 5:17 and Galatians 6: 15. However, there are various interpretations that appear on this word. By using a qualitative literature approach and descriptive method for the text of 2 Corinthians 5:17 it is found that Paul uses sentences in the present form, not the form that will come; "Who is in Christ, he is a new creation," not "Who is in Christ, he will be a new creation." The word kainos refers to a change in attitude, behavior, character and not in material/body. Next is that the word new creation is closely related to change. Change is very closely related to things that are psychological (unconscious mind), not things that are outward. In other words, change is related to things that are "from within" not "from outside" human life.